Estimativa da exigência hídrica do amendoim usando um modelo agrometeorológico - Assunção, Hildeu Ferreira da; Escobedo, João Francisco [UNESP] (My University, 2009)
In the experimental area of the Department of Environmental Sciences (21.85° S; 48.43° W; 786 m), in the School of Agronomical Sciences, UNESP, Botucatu, SP, an experiment was carried out using peanut (Arachis hypogaea L), cv. IAC-TATU-ST, to quantify the crop daily water requirements. During the peanut crop cycle, the environmental variables, such as rainfall, air temperature, air relative humidity, soil matric potential, soil heat flux and radiation balance, have been registered continually. These measurements were used to calculate the daily crop evapotranspiration, by the Bowen ratio method. The water replacement required by the peanut crop was done the dripping irrigation system, oriented by a dynamic agrometeorological model that computes the entrance and exit of water in the soil. During the peanut crop cycle, 9.0 mm of water was used from sowing to emergence; 67.0 mm of water, in the growth stage; 166.0 mm, in the flowering stage; 124.0 mm in the final stage and 46.0 mm from physiological maturity to harvest. Oot of 412.0 mm of the total consumption, 246.0 mm of water was supplied by irrigation and 166.0 mm by the rain. The grain yield was 3.15 t ha-1 for 15% of humidity, and the water use efficiency was 0.764 kg m-3.
Use of an agrometeorological model to computing the peanut water requirements
Keywords: Bowen ratio; Irrigation; Water balance; Water use efficiency; agrometeorology; air temperature; crop yield; drip irrigation; environmental factor; evapotranspiration; experimental study; numerical model; nut; relative humidity; water budget; water use; Botucatu; Brazil; Sao Paulo [Brazil]; Arachis hypogaea